Pengabaian Suami Dalam Pemberian Nafkah Istri - Aulil Amri (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2022)
There is an increase in divorce cases due to neglect of the wife's living at the Syar'iyah Court of Banda Aceh City every year. The husband is obligated to pay a living that he ignores because fulfilling a living is obligatory, and if he ignores it, that livelihood becomes a debt. The problems in this study are how the judge's consideration in the past demands for a living and the payment of the dowry that cannot be accepted/rejected, what are the consequences of the husband in the case of neglecting the wife's livelihood, and how is the analysis of the decision in the case of neglecting the husband in providing the wife's support. This research was conducted with a qualitative approach, the data that has been collected was analyzed through descriptive analysis method. The results of the research at the Syar'iyah Court of Banda Aceh City in the case of divorce, the wife may file a lawsuit which is her rights. It is the judge who determines and decides on the wife's lawsuit based on the judge's considerations.